The milestones of Qur’anic methodology in human and civilization development: An analytical comparative study on Fi Zilal al-Quran and al-Tahrir wa al-Tanwir / Mohamed Amine Hocini - Mohamed Amine , Hocini (2018)
This study is significant because it provides a comprehensive perception of the Qur’anic approach of human development and civilization to assist man perform his duties. The decline of the Ummah is mainly due to its deviation from the Holy Qur’an and searching for guidance from human sources. The departure is due to the lack of clarity concerning the Qur’anic method to human development and civilization. This underscores the need to derive and highlight the Qur’anic methodology in this regard for ease of application and to reap the fruits of a divinely inspired approach to living. This Study clarifies the Qur’anic methodology to human development and civilization through two books of Tafsir (exegeses of the Qur’an), Fi Zilal al Qur’an and al-Tahrirwa al-Tanwir. This research used the inductive, analytical and comparative approaches. The findings show that the Qur’anic method to human development and civilization as espoused in Fi Fi Zilal al Qur’an and al-Tahrirwa al-Tanwir is comprehensive and covered the most important issues. There are no significant differences between the views of Sayyid Qutb and Ibn Achuor. However, both neglected the physical aspect of human development and the mechanisms for development. The findings of the research also show that the Qur’an gives priority to human development as it is the basis of all development. These aspects of development consist of faith, spiritual, intellectual, ethical and physical aspects. The civilization development consists of the social, political and the economical aspects. Every aspect is developed through specific mechanisms. The Qur’anic approach not only develops human and establishes civilization, but rather sets up mechanisms to protect and preserve them from which can interrupt the development process. The Qur’anic approach to human development and civilization is unique and effective due to being al-Rabbāniyyah (divine) and compatible with the fitra (human instinct).